A Validity and Reliability of The START Triage Knowledge and Attitude Instrument in Medical Personnel and Health Workers - Faizatiwahida, Novia; Irnu, Julfilkar Adnan; Ayuningtyas, Pusparini Anggita; Hatta, Haslindar; Nurjannah, Intansari; Alim, Syahirul (Jurnal Berita Ilmu Keperawatan, 2024)
Medical and health personnel have the potential to play an important role in triage START in the event of a disaster. However, it is important to have an instrument in evaluating the level of knowledge and attitudes of medical and health dragons regarding the START triage. This instrument is essential for the development of a comprehensive and efficient START triage education program for medical and health personnel. Therefore, this study aims to assess the accuracy and consistency of knowledge and attitude instruments in conducting START triage for medical and health personnel. A cross-sectional study involving 100 respondents. This instrument is created through a literature review. The instrument totaled 10 items of statements on knowledge and 10 items of statements on attitudes categorized into 6 groups: 1) disasters; 2) START triage; 3) START triage principle; 4) START triage indicator; 5) START triage implementation procedure. The results of this study showed 100 participants, the majority of whom were female with an average age of 36 years. All participants are medical and health personnel. The instruments used in the study were validated through content validity (Pearson Product Moment) and biserial correlation. Utilizing internal consistency reliability, the study found satisfactory inter-item reliability for all knowledge items (0.70 – 0.73) and attitude items (0.86 – 0.90). Conclusion: these findings suggest that knowledge and attitudes in performing the START triage are important for medical and health personnel